The reality of Taibah University and the opinions of its leaders and affiliates on the obstacles and possible alternatives to increase and diversify the university’s funding in the American and British experiences - ALamri, Abdulaziz Yehia (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to investigate the status of alternative funding in Saudi Arabia using Taibah University as a model. specifically, the study tried to discover obstacles to alternative funding at Taibah University to suggest mechanisms to improve it in light of the experiences of advanced countries. to achieve the objectives of the study, the research used mix approach design using questionnaire and interview tools to collect data. The researcher sampled 140 participants consisting of deans, vice-deans, Faculty members, and employees of Taibah university. The items of the questionnaire and following up interview were developed by the researcher and validated by experts in the field. The SPSS version 25 was used to analyze the collected data to compute descriptive and inferential statistics. The results of the study showed that the major sources of funding for Taibah comes from the government (About 99%) while self-Generated resources represent early a small percentage (around 1%). The self-generated Resources come from three sectors: Tuition fees, investment, and Endowment. The result also showed the overall participants’ agreement on the obstacles to finding a Taibah in University is 3.95 out of 5. The major obstacles found are administrative bureaucracy (4.36) and the lack of the private scoter involvement in the field of education (4.18), among others. as for the use of experiences in developed countries as mean to alternative funding, there is a high (4. 12 out of 5) agreement among participants. The most agreed are the use of cost-sharing (4.53), and endowment (4.53). in light of these findings, the researcher made four recommendations for improvement and future studies. The first one is to Reduce the Administrative bureaucracy to facilitate self-fund generation and encouraging the private sector to invest in education. The second one is to focus more on investment strategies to make the university resources and donations more efficient. The third one is to make use of alternative schemes of funding from developed countries that can be adapted in the context of Saudi Arabia. The last one is to conduct further studies on the topic to help validate these findings and gain additional information based on which means to reduce reliance on government funding can be reduced.
Keywords: financing alternatives; obstacles; higher education; Taibah University